2010
DOI: 10.1186/1471-2164-11-337
|View full text |Cite
|
Sign up to set email alerts
|

A deletion mutation in bovine SLC4A2 is associated with osteopetrosis in Red Angus cattle

Abstract: BackgroundOsteopetrosis is a skeletal disorder of humans and animals characterized by the formation of overly dense bones, resulting from a deficiency in the number and/or function of bone-resorbing osteoclast cells. In cattle, osteopetrosis can either be induced during gestation by viral infection of the dam, or inherited as a recessive defect. Genetically affected calves are typically aborted late in gestation, display skull deformities and exhibit a marked reduction of osteoclasts. Although mutations in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 36 publications
(67 reference statements)
3
69
0
1
Order By: Relevance
“…Associations existed on 16 different chromosomes, some of which have previously been documented to be associated with calving traits (i.e. ss86324977), whereas others are novel previously unreported associations but have been reported to be associated with growth, skeletal development, birth weight and stature (Cole et al, 2009;McClure et al, 2010;Meyers et al, 2010). QTL regions that were solely associated with one trait were also identified facilitating direct genomic selection for these regions thereby possibly aiding in resolving known genetic antagonisms between the calving performance traits (Luo et al, 1999;Steinbock et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Associations existed on 16 different chromosomes, some of which have previously been documented to be associated with calving traits (i.e. ss86324977), whereas others are novel previously unreported associations but have been reported to be associated with growth, skeletal development, birth weight and stature (Cole et al, 2009;McClure et al, 2010;Meyers et al, 2010). QTL regions that were solely associated with one trait were also identified facilitating direct genomic selection for these regions thereby possibly aiding in resolving known genetic antagonisms between the calving performance traits (Luo et al, 1999;Steinbock et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Two of these genes, SLC26A7 and TMEM64 have been documented to be associated with cartilage and bone development in humans (Lohi et al, 2002;Kim et al, 2013) suggesting that these genes may be responsible for the many morphological abnormalities associated with perinatal mortality. In cattle, a deletion in a similar gene (SLC4A2) has been shown to be associated with osteoporosis in Red Angus cattle (Meyers et al, 2010). Osteoporosis is a bone disorder observed in humans and many other animals and can be inherited as a recessive defect.…”
Section: Chromosome 18mentioning
confidence: 99%
See 2 more Smart Citations
“…The coat colours of horse, pig and sheep are partly determined by CNVs (Clop et al 2012), and milk production (Xu et al 2014), female fertility failure (Kadri et al 2014), osteoporosis (Meyers et al 2010), abortions and stillbirth in cattle have been shown to be influenced by CNVs. CNVs have been identified in different cattle breeds, including African, Indicine and Taurine breeds (Matukumalli et al 2009), andBae et al (2010) and Fadista et al (2010) created two CNV maps of the bovine genome using SNP genotyping and CGH arrays.…”
Section: Introductionmentioning
confidence: 99%